Legal Rights and Protections for Victims of Sexual Violence: A Study of the Role of the Sorong City DP3A - Chintia Manurung; Sokhib Naim; Bayu Purnama (Journal of Law Justice (JLJ), 2026)
This study aims to analyze the authority of the Sorong City Office for Women’s Empowerment and Child Protection (DP3A) in providing protection to victims of sexual violence. Previous studies have generally addressed the protection of victims of sexual violence in general terms but have not specifically examined the implementation of the DP3A’s authority regarding prevention, response, and rehabilitation of victims at the local level. The method used is empirical research, employing data collection techniques such as interviews, observations, and a review of documentation regarding the implementation of the duties and functions of the Sorong City DP3A. The novelty of this study lies in its focus on analyzing the implementation of the Sorong City DP3A’s authority in the prevention, handling, and rehabilitation of victims of sexual violence, while also identifying the obstacles faced in its implementation at the local level. The results of the study indicate that the Sorong City DP3A has exercised its authority through legal assistance, psychological counseling services, social protection, and prevention programs in the form of public awareness campaigns and advocacy efforts. However, the exercise of these authorities still faces challenges in the form of budget constraints and the lack of safe house facilities in the region. The conclusion of this study indicates that the DP3A plays a crucial role in protecting victims of sexual violence; however, strengthening budgetary support, providing supporting facilities, and enhancing interagency coordination are necessary to ensure that victim protection efforts can be carried out more effectively.